2010
DOI: 10.1002/cphc.201000294
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hydroperoxy Species as Reaction Intermediates in the Electrochemical Evolution of Oxygen on Gold

Abstract: Efficient electrochemical splitting of H 2 O to O 2 and H 2 fuels has become an important goal in the quest for a renewable source of energy.[1] A major source of the inefficiency of this process is the significant overpotential associated with the anodic oxygen evolution reaction (OER). Understanding the mechanism of the OER could help in identifying the elementary processes contributing to OER overpotential and their relationship to the anode composition and morphology. While the OER has been investigated bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
160
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(180 citation statements)
references
References 30 publications
17
160
2
1
Order By: Relevance
“…Considering that this AuOOH species was observed at potentials where the A2 process occurs, E>1.6 V versus RHE, it is highly likely that they are connected. That is, the AuOOH species observed by Bell [78] and Koper [55] and the active hydroperoxy intermediate proposed by Burke [63] to account for the A2 process are one and the same. Fig.…”
Section: Oxygen Evolution Mechanismmentioning
confidence: 63%
See 1 more Smart Citation
“…Considering that this AuOOH species was observed at potentials where the A2 process occurs, E>1.6 V versus RHE, it is highly likely that they are connected. That is, the AuOOH species observed by Bell [78] and Koper [55] and the active hydroperoxy intermediate proposed by Burke [63] to account for the A2 process are one and the same. Fig.…”
Section: Oxygen Evolution Mechanismmentioning
confidence: 63%
“…To date, atomic-scale insight into the OER has proven difficult due to the lack of significant spectroscopic evidence of intermediates. However, recent surface-enhanced Raman spectroscopy (SERS) studies provide convincing evidence for metal OOH intermediates on Au, Ni and Co substrates [55,[78][79][80]. Specifically, Bell and coworkers [78] found that a characteristic v(O-O) band of quite low intensity at 815-830 cm −1 could be observed for a Au substrate at potentials greater than ca.…”
Section: Oxygen Evolution Mechanismmentioning
confidence: 96%
“…Heating THF solutions of 2 and 4 for 16 h at 60°C leaves the compounds unchanged. Complexes 2 and 4 are also stable to 44 assigned a Raman band at 820 cm À 1 to a surface-bound OOH species.…”
Section: Resultsmentioning
confidence: 99%
“…Hydroperoxy species have been detected as intermediates in the electrochemical evolution of oxygen on gold using surface-enhanced Raman spectroscopy (SERS) [22] and in the photocatalytic oxidation of water on IrO2 nanoclusters [23]. Hydroperoxy species can desorb from the transition metal active sites to the solution, which may result in a number of reactions.…”
Section: Introductionmentioning
confidence: 99%